Adapting the Guilt About Parenting Scale (GAPS) to Turkish culture: Validity and reliability study - ERYİĞİT, DERYA; AYDOĞDU, BİLGE NURAN; EKŞİ, HALİL (My University, 2022)
The aim of this study is to adapt the Guilt About Parenting Scale (GAPS), developed by Haslam et al. (Journal of Child and Family Studies, 29(3), 880-894, 2020), to Turkish by validity and reliability analysis. The scale was applied to 430 parents, and its corrected item-total test correlations ranged from .55 to .71 (p < .01). As a result of Confirmatory Factor analysis, the values for the goodness-of-fit indices were found to have acceptable values (chi(2) = 70.65, SD = 27, RMSEA = .06, CFI = .97, and SRMR = .02). The GAP\"s Cronbach alpha of internal consistency was seen to be alpha = .893. Within the scope of the criterion-related validity study, a positive relationship at the .60 level was detected between the Maternal Employment Guilt Scale (MEGS) (Yuce-Selvi & Kantas Is, Guc: Endustri Iliskileri ve Insan Kaynaklari Dergisi, 21(1), 28-52, 2019) and the total score from the GAPS. The results of the research show the Turkish form of the GAPS to be a valid and reliable measuring tool.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); General Psychology; Psychology (miscellaneous); Social Sciences & Humanities; Guilt about parenting; Guilt; Parenting guilt; Confirmatory factor analysis; Validity; Reliability; Scale; FEELINGS; MOTHERS; GENDER